Assessing and Encouraging Progressivity of Post-Mining Activities Arrangements - Sigit Wibowo; Lita Tyesta ALW; Kornelius Benuf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
Mineral and coal mining activities have an impact on environmental damage. So that to overcome the environmental damage, a policy is made regarding post-mining activities. In essence, post-mining activities are an effort to restore the functions of the natural environment and social functions and are adjusted to local conditions in the mining area. However, the policy that was previously regulated in the old Mineral and Coal Law has not been effectively implemented. The existence of regulations regarding post-mining activities in the new Mineral and coal Law is expected to be more progressive. The problem is how is the progress of regulations regarding post-mining activities in the new Mineral and Coal Law? This problem will be examined in this paper using normative juridical research methods. Based on the research results, it is concluded that there is no progressive regulation of post-mining activities in the new Minerba Law, so it is necessary to have progressive regulations regarding post-mining activities in the future.